Interleukin-6 Induced Proliferation Is Attenuated by Transforming Growth Factor-β-Induced Signaling in Human Hepatocellular Carcinoma Cells - Srivastava, Abhilasha; Sharma, Harshita; Khanna, Simran; Sadhu Balasundaram, Tejasvini; Chowdhury, Shibasish; Chowdhury, Rajdeep; Mukherjee, Sudeshna (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is often associated with an inflammatory setting. A plethora of cytokines are secreted in this milieu, actively contributing to the progression of the disease; however, the extent of cytokine interaction and how it contributes to HCC development remains an enigma. In this regard, our analysis of available patient-derived data suggests that cytokines like interleukin-6 (IL-6) and transforming growth factor-beta (TGF-β) are enriched in HCC. We further analyzed the effect of these cytokines independently or in combination on HCC cells. Importantly, IL-6 was found to induce a STAT-3-dependent proliferation and mediate its pro-proliferative effects through activation and direct interaction with the p65 subunit of NFkB. Alternatively, TGF-β was found to induce a SMAD-dependent induction of epithelial to mesenchymal transition (EMT) coupled to growth arrest in these cells. Interestingly, the simultaneous addition of IL-6 and TGF-β failed to profoundly impact EMT markers but resulted in attenuation of IL-6-induced pro-proliferative effects. Analysis of the putative molecular mechanism revealed a decrease in IL-6 receptor (IL-6R) transcript levels, reduced expression of IL-6-induced STAT-3, and its nuclear localization upon addition of TGF-β along with IL-6. Consequently, a reduced p65 activation was also observed in combination treatment. Importantly, SMAD levels were unperturbed and the cells showed more TGF-β-like features under combination treatment. Finally, we observed that TGF-β resulted in enrichment of repressive chromatin mark (H3K27me3) coupled to growth arrest, while IL-6 induced an open chromatin signature (H3K4me3) associated with an enhanced expression of EZH2. Overall, for the first time, we show that TGF-β attenuates IL-6-induced effects by regulating the receptor level, downstream signaling, and the epigenome. Understanding the complex interactions between these cytokines can be imperative to a better understanding of the disease, and manipulation of cytokine balance can act as a prospective future therapeutic strategy.